PRIMITIVE DEFENCES AND VIOLENCE IN AFRICA: AN ANALYSIS OF EMECHETA’S THE JOYS OF MOTHERHOOD AND EZEIGBO’S TRAFFICKED (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Most times, the lower class people in Africa are faced with overbearing emotional and physical pains and this is due to the problem posed by the double patriarchal nature of the society, obscure traditions and failed leadership, which cause mass poverty through the high rate of inflation, low per capita income, unemployment, underemployment and rapid population growth. Akachi Adimora-Ezeigbo’s Trafficked and Buchi Emecheta’s The Joys of Motherhood, expose the above-listed hurting circumstances, their effect on the character’s inner self and the character’s outward reaction. Using Sigmund Freud's discusses on ego psychological defense mechanisms; the study identifies some defenses that are prone to result into violence, which is common among young, inexperienced and severely distressed individuals. In this case, characters employ some reactive primitive defenses that enable them to transfer their psychological pains to themselves, some other items around them or persons outside themselves. However, it is noticed that by the use of mature defenses, these painful anxiety-causing circumstances are subdued. The study, therefore, recommends a change of thought patterns and an improved standard of living for the people in other to quell their psychological pains and reduce the rate of violence in Africa.
Keywords: Poverty,Anxiety,Defense,Violence